2021
DOI: 10.3390/ani11041155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rosemary (Rosmarinus officinalis) and Blackcurrant Extracts (Ribes nigrum) Supplementation on Performance Indices and Oxidative Stability of Chicken Broiler Meat

Abstract: The effects of dietary supplementation with extracts of rosemary (RO) and blackcurrant (BC) on the performance indices and the oxidative stability of broiler meat were investigated during a 35-d experiment. For the experiment, 120 one-day-old male Hubbard Flex broiler chicks were randomly allocated to 5 experimental groups (control group and 4 treatments, each in 6 replications, 24 birds per group, 4 birds per replicate) and fed control starter and grower diets or basal diets containing two concentrations (2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…As shown in Figure 1, no significant among-group differences were noted, but group B tended to have a higher body weight. Similar findings have been reported by Sierżant et al (2021), who confirmed no significant effect on the average body weight of broilers after supplementation of diets with two concentrations (0.25 and 0.5 %) of rosemary and blackcurrant extracts. Petricevic et al (2018) reported that the use of 0.2% rosemary in diets caused no significant differences in average daily gain, but 0.4 and 0.6% supplemented rosemary powder in broiler feed could improve average daily gain and feed conversion ratio.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Figure 1, no significant among-group differences were noted, but group B tended to have a higher body weight. Similar findings have been reported by Sierżant et al (2021), who confirmed no significant effect on the average body weight of broilers after supplementation of diets with two concentrations (0.25 and 0.5 %) of rosemary and blackcurrant extracts. Petricevic et al (2018) reported that the use of 0.2% rosemary in diets caused no significant differences in average daily gain, but 0.4 and 0.6% supplemented rosemary powder in broiler feed could improve average daily gain and feed conversion ratio.…”
Section: Resultssupporting
confidence: 90%
“…Additionally, UA reduced the TC level, suggesting that RA and UA may have an effect on lipid metabolism in pigs. Previous studies have shown positive effects of rosemary extract ( Yesilbag et al., 2011 ), RA and UA on growth performance in broiler chickens ( Cheng, 2018 ; Shang et al., 2022 ), while other studies showed that dietary RA showed no significant effect on growth performance in chickens ( Sierżant et al., 2021 ). In the current study, there was no statistically significant difference in growth performance among the groups, although the ADG was 0.83 kg/d and 0.91 kg/d in the CTL and RA goup, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rosemary decreased production of secondary lipid oxidation compounds like hexanal by up to 32% compared to control meat. The enhanced antioxidant capacity extended shelf life (121).…”
Section: Meat Qualitymentioning
confidence: 99%